Mannanase production by Aspergillus niger USM F4 via solid substrate fermentation in a shallow tray using palm kernel cake as a substrate - Syarifah Ab Rashid; Darah Ibrahim; Ibrahim Che Omar (2012)
Aims: A local fungal isolate, Aspergillus niger USM F4 produced high level of mannanase activity when cultivated in a shallow tray system (45 x 40 x 7 cm3) using palm kernel cake (PKC), an easily available cheap agricultural waste which are found abundantly in Malaysia. Methodology and Results: A range of 0.25 to 1.5 cm bed heights were investigated in tracking in the most suitable condition and maximum production of mannanase. The highest mannanase production of 918.68 U/g substrate was obtained on the fifth day of cultivation after using all the optimised cultural conditions that consisted of 400 g of PKC that equivalent to 0.50 cm of substrate thickness with the particle size of ≤ 0.5 mm, moisture content of 80% (w/w) with the addition of 2% (w/w) molasses as a carbon source and 4% (w/w) ammonium nitrate as a nitrogen source, inoculums size of 1x107 spores/ml, with once at every 24 h of mixing frequency and cultivation temperature at room temperature 30±2 °C. Conclusion, significance and impact of study: The results obtained from this study showed that a shallow tray system was suitable to be used for getting highest enzyme production in SSF. Besides using a bigger volume of substrate, the correct substrate bed height is also important.